ANALISIS STRATEGI PENURUNAN KEHILANGAN AIR PADA DMA 02 UTARA PERUMDA AIR MINUM KOTA PADANG - Huda, Miftakhul; Yuniarto, Adhi; Sundoro, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
The level of water losses or Non-Revenue Water (NRW) of Perumda Air Minum Kota Padang is still relatively high at 28.02% (2022), this value is still above the national target (25%). This study aims to analyze strategies to reduce water losses, especially in DMA 02 Utara Perumnas Belimbing. The research was conducted by collecting data in the form of discharge and pressure in the DMA, as well as collecting data on customer water usage, number and spread of customers, distribution pipe networks, and elevation heights. Data analysis in the form of simulations using Epanet 2.2 to determine strategies that can be applied. Analysis of the level of reduction in water loss obtained after the implementation of the strategy was carried out using the FAVAD (Fixed and Variable Area Discharge) method. The results showed that after the implementation of the water loss reduction strategy, the level of physical water loss in DMA 02 Utara Perumnas Belimbing was reduced by 16.41% from the original 84,885 m³/month down by 13,929.81 m³/month to 70,995.19 m³/month. So, the strategy applied in this study is feasible to use to reduce water loss